Aeration of water with oxygen microbubbles and its purging effect. (19th July 2017) - Yamashita, Tatsuya; Ando, Keita
Abstract : In this paper, we apply aeration with oxygen microbubbles to tap water; the intent is to quantitatively evaluate whether nitrogen gas originally dissolved in the water under the atmosphere is purged by the aeration with oxygen microbubbles. Oxygen microbubbles are continuously injected into the circulation system of tap water open to the atmosphere. While the concentration of dissolved oxygen (DO) can be detected by a commercial DO meter, that of dissolved nitrogen (DN) is unavailable. To detect the DN level, we observe the growth of millimetre-sized gas bubbles nucleated at glass surfaces in contact with the aerated water and compare it with the multi-species theory of Epstein and Plesset where the (unknown) DN concentration is treated as a fitting parameter. In the theory, we solve binary diffusion of each gas species (oxygen or nitrogen) in the water independently, under the assumption that the dissolved gases are sufficiently dilute. Comparisons between the experiment and the theory suggest that the DN in the water is effectively purged by the oxygen aeration. The supplemental experiment of aeration with nitrogen microbubbles is also documented to show that the DO can be effectively purged as well.